Search for single vector-like B quark production and decay via B ? bH(b(b)over-bar) in pp collisions at ?s=13 TeV with the ATLAS detector - Çakır, Affan (SPRINGER, 2023)
A search is presented for single production of a vector-like B quark decaying into a Standard Model b-quark and a Standard Model Higgs boson, which decays into a b (b) over bar pair. The search is carried out in 139 fb(-1) of root s = 13 TeV proton-proton collision data collected by the ATLAS detector at the LHC between 2015 and 2018. No significant deviation from the Standard Model background prediction is observed, and mass-dependent exclusion limits at the 95% confidence level are set on the resonance production cross-section in several theoretical scenarios determined by the couplings c(W), c(Z) and c(H) between the B quark and the Standard Model W, Z and Higgs bosons, respectively. For a vector-like B occurring as an isospin singlet, the search excludes values of c(W) greater than 0.45 for a B resonance mass (m(B)) between 1.0 and 1.2 TeV. For 1.2 TeV < m(B <) 2.0 TeV, c(W) values larger than 0.50-0.65 are excluded. If the B occurs as part of a (B, Y) doublet, the smallest excluded c(Z) coupling values range between 0.3 and 0.5 across the investigated resonance mass range 1.0 TeV < m(B) < 2.0 TeV.
Keywords: Vector-Like Quarks; Beyond Standard Model; Exotics; Hadron-Hadron Scattering